3D Integration for NoC-based SoC Architectures - Sheibanyrad, Abbas.; Sheibanyrad, Abbas.; Pétrot, Frédéric.; Pétrot, Frédéric.; Jantsch, Axel.; Jantsch, Axel. (Integrated Circuits and Systems,, 2011)
Back Cover Copy SERIES: Integrated Circuits and Systems 3D-Integration for NoC-based SoC Architectures by: (Editors) Abbas Sheibanyrad Frédéric Petrot Axel Janstch This book investigates on the promises, challenges, and solutions for the 3D Integration (vertically stacking) of embedded systems connected via a network on a chip. It covers the entire architectural design approach for 3D-SoCs. 3D-Integration technologies, 3D-Design techniques, and 3D-Architectures have emerged as topics critical for current R&D leading to a broad range of products. This book presents a comprehensive, system-level overview of three-dimensional architectures and micro-architectures. •Presents a comprehensive, system-level overview of three-dimensional architectures and micro-architectures; •Covers the entire architectural design approach for 3D-SoCs; •Includes state-of-the-art treatment of 3D-Integration technologies, 3D-Design techniques, and 3D-Architectures.